1998
DOI: 10.1002/(sici)1521-4095(199808)10:11<877::aid-adma877>3.0.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

High Density Rechargeable Lithium-Ion Batteries Self-Assembled from Graphite Oxide Nanoplatelets and Polyelectrolytes

Abstract: The construction of a high‐capacity intercalating cathode via an entirely new approach is reported—the self‐assembly of nanometer‐thick polyelectrolytes and graphite/graphite oxide nanoplatelets on a conducting substrate. The advantages of this approach as well as the charging and discharging behavior of a high‐density (1232 mAhg–1 of graphitic carbon) rechargeable lithium‐ion battery based on this cathode are described. This electrochemical cell holds commercial promise as it may be readily scaled up to an ec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
135
1
3

Year Published

1999
1999
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 217 publications
(141 citation statements)
references
References 8 publications
2
135
1
3
Order By: Relevance
“…Thin film applications range from coatings, compatibilization and surface protection [59], enzyme immobilization [60], biosensors [61], gas separation membranes [62], high charge density batteries [63], modified electrodes [64], etc. Polyelectrolyte multilayer microcapsules, on the other hand, may be used in areas such as medicine, delivery systems [65], catalysis, micro-containers and reactors [66].…”
Section: Application Potentials Of Poly(ferrocenylsilane) Multilayer mentioning
confidence: 99%
“…Thin film applications range from coatings, compatibilization and surface protection [59], enzyme immobilization [60], biosensors [61], gas separation membranes [62], high charge density batteries [63], modified electrodes [64], etc. Polyelectrolyte multilayer microcapsules, on the other hand, may be used in areas such as medicine, delivery systems [65], catalysis, micro-containers and reactors [66].…”
Section: Application Potentials Of Poly(ferrocenylsilane) Multilayer mentioning
confidence: 99%
“…13 Graphene, is a flat monolayer of carbon atoms tightly packed into a two-dimensional (2D) honeycomb lattice, and can be considered as a basic building block for other kinds of graphitic materials, such as 0D fullerenes, 1D nanotubes or 3D graphite. 14 Because of their novel and fascinating properties, such as exceptional thermal and mechanical properties, as well as high electrical conductivity, graphene, as a ''rising star'' material 15 has been extensively studied for synthesizing nanocomposites 16 and fabricating various microelectrical devices, such as batterys, 17 field-effect transistors, 18 ultrasensitive sensors, 19 and electromechanical resonators. 20 Recent investigations have shown that graphene exhibits favorable electrochemical activity towards many analytes, and it minimizes passivation, improves high electrontransfer and avoides interferences in a wide range of electrochemical sensing and biosensing applications.…”
Section: Introductionmentioning
confidence: 99%
“…The current surge of interest to graphite oxide is due to not only its application as a prospective material for electrodes, membranes, and polymer additives [2][3][4][5][6][7] but also to a new avenue which opened after the discovery of the unique properties of graphene [8][9][10]. Contrary to many other carbon materials, graphite oxide is hydrophilic and is capable of forming colloidal solutions in water, spirits, and other polar solvents, where GO splits into thin sheets of up to one carbon layer thickness [11][12][13].…”
Section: Introductionmentioning
confidence: 99%